Experimental Study of the Low-Cycle Fatigue in Double-Walled Hollow Pipe Members - Lu Zhaohong; Zunce Wang; Yan Xu; Gao Shanshan; Han Lianfu (Advances in Civil Engineering)
This paper introduces a double-walled hollow pipe (DWHP) that demonstrates good corrosion resistance and mechanical properties and that can be used in pipeline transportation and structural stress components in marine, freshwater, and corrosive environments. We designed and machined the specimens to meet the bending bearing capacity using a cross section method. We conducted low-cycle loading tests of the specimens to investigate the energy dissipation capacity of the DWHP, the effects of different geometrical parameters, and the concrete-filled strength of the DWHP on energy dissipation capacity. The results show that the failure forms of the specimens are similar. The geometrical characteristics of the specimens, the cohesive function between the concrete and the steel plate, and the strength of the concrete-filled pipe showed a significant influence on the mechanical properties of the specimens. Hysteretic curves are plump and possess a high capacity for energy dissipation. The energy dissipation capacity of the specimen decreases with an increase in the slenderness ratio. The slope of strength degradation decreases with any increase in the strength of the concrete-filled pipe. We optimized the section design of the component by improving the constraint effect coefficient, and we effectively improved its stability by adding stiffeners to the inner side of the outer wall of steel.